Mammalian conservation: scientific frontiers and socio-political pitfalls - Lidicker, William (THERYA, 2014)
Introduction: The frontiers of conservation biology are rapidly advancing. This is partly because of scientific achievements, but also it is because the human predicament continues to deteriorate in spite of heroic but inadequate efforts to make the human enterprise sustainable. Of greatest importance is the need to escape from the confrontational mode that pervades our social and political discussions. We must trade this conflict for a realization that there is only one objective for all of humanity, and that is the sustainability of human civilization. Mammalian conservation can play a major role in this struggle, but to do this we must take the initiative to promote meaningful dialogue with politicians, policy makers, economists, sociologists, and the public at large. At the same time, we must continue to be at the frontiers of our science while not neglecting the pursuit of much needed basic research on taxonomy, life history, and distribution of the world’s mammals. Some social, political, and strategic considerations: Themes suggested to enhance such communication are: non-confrontational cooperation, life support services, optimism, systems thinking, and adapting to various political regimes. Frontiers of conservation science: Eight leading edge topics are suggested for the science component of conservation: 1) community tipping points, 2) trophic cascades, 3) landscape or ecoscape perspective, 4) role of common species in community dynamics, 5) climate change complications, 6) role of genetics, 6) social dynamics, 7) microorganism synergisms, and 8) translocations. Mammalian conservationists are poised to play a significant role in humanity’s efforts to confront the myriad of intertwined problems that we face. Given that humans belong to the same taxonomic class that is the subject of our expertise, we have special responsibility to provide that leadership. Key words: captive breeding, climate change, community tipping points, conservation genetics, cooperation, landscape perspective, life support services, microbiota synergisms, new conservation, optimism, social behavior, sustainable civilization, systems perspective, translocations, trophic cascades.